Phytochemical screening of bunga rosella (Hibiscus sabdariffa L) and antimicrobial activity test - Hermawan Purba; Helen Anjelina Simanjuntak; Risanti Situmorang (Pascasarjana Universitas Negeri Medan, 2020)
The purpose of this study was to determine the antimicrobial activity of rosella infusa (Hibiscus sabdariffa L.). Antimicrobial inhibition test using infusa of rosella (Hibiscus sabdariffa L.) against Staphylococcus aureus and Escherichia coli bacteria at a concentration of infusa 100%; 75%; and 50%. The concentration has highest potential antibacterial of infusa for Staphylococcus aureus is 100% witch has diameter of 13.6 mm and for Escherichia coli bacteria is 100%, its show that diameter of zone inhibitory zone is 13.3 mm. The Results of phytochemical screening show that infusa of rosella (Hibiscus sabdariffa L.) contains flavonoids, saponins, and tannins. Based on the data above show that the infusa of rosella flower has high antibacterial potential. Keywords: Hibiscus sabdariffa L., antimicrobial activity, Staphylococcus aureus, Escherichia coli